A proposed audit program for a comprehensive electronic banking system based on business risks : applied research (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research seeks to identify the comprehensive electronic banking system and the role of the auditor in light of the customer's application of electronic systems that depend on the Internet in providing its services, as a proposed audit program has been prepared in accordance with international auditing controls and standards based on the study of the customer's environment and the analysis of external and internal risks in the light of financial and non-financial indicators, the research reached a set of conclusions, most notably, increasing the dependence of banks on the comprehensive banking system for its ability to provide new and diverse banking services, The researcher suggested several recommendations, the most important of which is the need for management to increase investment in information technology and monitor the financial allocations required to implement the comprehensive system according to a specific plan and schedule and monitor deviations in the application, their causes and ways to address them, with the need for the auditor to adopt an audit program in line with the size of the client's internal and external risks and analyze them to determine the risks that threaten the continuity of the client's activity and the size of the material misrepresentations.  The remaining ones that extend to the financial statements.